Village Government Policy Model to Reduce Stunting Rates - Harmono, Harmono; Harliyanto, Rois; Anggraini Daulay, Annisa; Justitia, Triana; Karina, Siska; Ika Putri, Dessy; Fasya Khoirunissa, Alisha; Dawam Mubarok, Uba (Jurnal Legisci, 2024)
St stunting is a serious challenge to health development in Indonesia, especially in rural areas. This study uses an empirical juridical approach, which is a legal research method that connects written regulations with reality in the field through qualitative descriptive analysis, to analyze village government policies in reducing stunting rates in Astanalanggar Village and Tegalgubug Village, Cirebon Regency. With the aim of identifying challenges in its implementation, assessing the effectiveness of existing policies, and providing recommendations based on the needs of rural communities, research data was obtained through interviews and direct observation. The results of the study show that despite national and regional regulations such as Presidential Regulation Number 72 of 2021 and Cirebon Regent Regulation Number 25 of 2023, there are no special policies at the village level that regulate stunting control. Intervention programs implemented, such as supplemental nutrition, blood-boosting tablets, and nutrition education, face obstacles, including low public awareness, limited access to health facilities, and cultural barriers. Tegalgubug Village has succeeded in reducing stunting rates through collaborative approaches and innovative programs such as "BESTI ONCE," while Astanalanggar Village still faces various challenges in program implementation. This study recommends strengthening cross-sector coordination, increasing public education, and optimizing local resources to improve policy effectiveness. A data-based approach by paying attention to the local conditions of each village is the key to reducing stunting rates in a sustainable manner.